1998
DOI: 10.1016/s0014-5793(98)00049-0
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular carbonyls in human stratum corneum: a biomarker for environmental oxidant exposure?

Abstract: The presence of stratum corneum carbonyls may serve as an intrinsic dosimeter for environmental oxidative damage to skin. To investigate the accumulation of carbonyls in human stratum corneum, skin was tape-stripped, then tapes were sequentially incubated with 2,4-dinitrophenyl hydrazine (DNPH), rat anti-DNP, mouse anti-rat IgG conjugated with alkaline phosphatase, p-nitrophenyl phosphate and absorbance (405 nm) measured and carbonyls estimated. Stratum corneum exposed in vitro to oxidants: hypochlorous acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 22 publications
3
34
0
Order By: Relevance
“…Therefore, it is difficult to estimate its effect on the skin in vivo. Thiele et al [10,24] have shown that sodium hypochlorite can introduce protein carbonyls into the SC in vitro. Thus, we used sodium hy- Acrolein treatment decreases bound water content in the SC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult to estimate its effect on the skin in vivo. Thiele et al [10,24] have shown that sodium hypochlorite can introduce protein carbonyls into the SC in vitro. Thus, we used sodium hy- Acrolein treatment decreases bound water content in the SC.…”
Section: Discussionmentioning
confidence: 99%
“…Catalase is one of the foremost antioxidant defense enzymes in the stratum corneum, and it is closely related to skin conditions [11][12][13] . Proteins in the stratum corneum, such as keratins, are modified by oxidation or glycation reactions to produce carbonylation proteins [14][15][16] . Therefore, SCCP is an excellent marker to show the degree of skin damage due to oxidative stress, and it has been reported that SCCP levels increase at sun-exposed body sites [17] .…”
Section: Differences In Susceptibility Tomentioning
confidence: 99%
“…The skin and the respiratory tract are the animal organs most direcdy exposed to oxidant air pollutants. Although numerous studies have documented the effects of oxidants on lungs, and have to some extent directed attention to the importance of the respiratory tract lining fluids (RTLFs) (18)(19)(20)(21)(22), only a few studies have described possible oxidative pollutant effects on cutaneous tissues (23)(24)(25)(26).…”
Section: Structural Considerationsmentioning
confidence: 99%
“…The skin and the respiratory tract are the animal organs most direcdy exposed to oxidant air pollutants. Although numerous studies have documented the effects of oxidants on lungs, and have to some extent directed attention to the importance of the respiratory tract lining fluids (RTLFs) (18)(19)(20)(21)(22), only a few studies have described possible oxidative pollutant effects on cutaneous tissues (23)(24)(25)(26).RTLFs vary in different levels of the respiratory tract. The thickness of these layers has only been estimated, not rigorously Environmental Health Perspectives * Vol 106, Supplement 5 * October 1998 1241 whereas in the distal bronchoalveolar regions, RTLF depth is only 0.2 to 0.5 pm (18,(27)(28)(29) (69,70).…”
mentioning
confidence: 99%